C-C and C-H bond cleavage reactions in acenaphthylene aromatic molecule, an ab-initio density functional theory study - Shanshal, Muthana Abduljabbar; Yusuf, Qhatan Adnan (European Journal of Chemistry, 2019)
The ab-initio DFT method (B3LYP) is applied to the study of the C-C and C-H bond cleavage reactions in acenaphthylene molecule. It is found that the C-C bond cleavage proceeds via a singlet aromatic transition state, compelled through a disrotatoric ring opening reaction. A sigmatropic H atom shift follows the transition state in some of these reactions, where the formation of a methylene -CH2,acetylenyl-, allenyl- or butadienyl moiety in the final product is possible. The calculated activation and reaction energies for the C-C ring opening are 164-236 and 52-193 kcal/mol, respectively. The calculated cleavage reaction energies for the C-H bonds are 117-122 kcal/mol and the activation energies are 147-164 kcal/mol.